Welcome to Class - Cornelia Linderoth; Carl-Johan Stenberg (Confero: Essays on Education, Philosophy and Politics)
This essay draws on recent work on artificial intelligence (AI) in education. Using education fiction as a mode for discussion, the essay explores a future shaped by datafication, rationalization, effectivization and management-by-data. It begins by looking at the social dynamics of AI and its implementation in educational settings. Additionally, the essay introduces two education fiction narratives inspired by common sociotechnical imaginaries on AI in education, as well as the authors’ previous engagement with interviewing teachers on the subject. These narratives highlight the role of AI designers and the EdTech Industry, revealing how the machinations of data sciences are influencing the educational landscape. Lastly, we emphasize the importance of involving teachers in defining what technology should, and should not, be in the educational infrastructure of the future.